A study on the impact of fiscal decentralization on carbon emissions with U-shape and regulatory effect - Jing Xia; Rita Yi Man Li; Xuegang Zhan; Lingxi Song; Weijia Bai (Frontiers in Environmental Science, 2022)
The Chinese government set a goal in 2009 to cut carbon emissions by 40–45 percent of 2005 GDP per unit by 2020. The role of fiscal decentralization reform in strengthening environmental governance has gained importance. This paper explored the impact of fiscal decentralization reform from 2010 to 2019 on carbon dioxide emissions in China. We utilized the first-order differential dynamic panel econometrics model to examine the correlation between fiscal decentralization and carbon dioxide emission under fiscal imbalance and transfer indirect effects. The findings revealed that 1) fiscal imbalance reduced CO2 emissions due to the decentralization of revenue, and expenditure asymmetry undermined CO2 emissions control. 2) The central government’s transfer payments offset the negative consequences of a fiscal imbalance. The fiscal decentralization of the government caused a difference between regional income and expenditures in the budget. However, it could affect local government expenditure on carbon emission control through central transfer payments, which could restrain carbon emissions and control environmental pollution. 3) The impact of fiscal decentralization on carbon dioxide emissions was influenced by the industrial structure with the U-Shape effect. This was because the adjustment of the industrial structure was cross-term. In the early stage of the industrial structure adjustment, there was a significant decline in coal consumption demand and carbon emissions reduced. However, as the proportion of the secondary industry increased, there was a significant positive correlation between the secondary sector and carbon dioxide emissions in China. Our findings have important policy implications. First, while the promotion of Chinese officials is based on local GDP performance, locals may introduce green GDP as the criterion for rating governments’ performance. Second, local governments should improve environmental governance by increasing technical, environmental protection, and innovation investment. All in all, the findings provide a theoretical basis for relevant research and policy suggestions for China.